Utilization of Waste From Shells Placuna Placenta For The Production of Hydroxyapatite Using The Precipitation Method - Khusnul Mubarok; Muhammad Gary Raditya; Ketut Sumada (Jurnal Serambi Engineering, 2026)
The problem in Indonesia of Placuna Placenta clam shell waste encouraged the development of this research. The aim was to determine the ratio of calcium (Ca) content to phosphorus (P) content in scallop shell waste using the H3PO4 addition precipitation method. The Ca content of scallop shell waste was 98.71%, still within the set quality standard of 95-98%. The international standard for Hydroxyapatite is the Ca/P atomic ratio of 1.61-1.76 mol/mol. Characterization included hydroxyapatite test, Scanning Electron Microscope-Energy Dispersive X-ray (SEM-EDX). The results showed that the volume of H3PO4 that approached the results of Hydroxyapatite was 2 ml at a stirring speed of 200 RPM with a pH of 12, resulting in a Ca/P ratio of 1.79 mol/mol with a final Ca content of 1.105 mol and a final P content of 0.617 mol. However, the addition of 10 ml of H3PO4 volume, Ca/P ratio of 1.60 mol/mol with a final Ca content of 0.985 mol and a final P content of 0.615 mol, resulted in the formation of hydroxide complexes such as [Ca10(PO4)6(OH)2]− soluble in water, causing the weight of the precipitate to decrease even though the Ca content in the filtrate decreased. This study also found a relatively optimal precipitation time at a stirrer rotation speed of 300 RPM ensuring constant results. The resulting Ca10(PO4)6(OH)2 precipitate has the potential to be further utilized in various applications, such as bone formation, bone and dental implants, in the pharmaceutical field.